The opposite and the alteration in the novel (Al-Tajlayat) For Jamal Al-Ghitani (Journal of Hama University, 2021)
The purpose of the analysis that the researcher seeks from studying the structure of reversal and switching in the novel (The Manifestations) is to reveal the style of Jamal Al-Ghitani from the face in which he is not shared by anyone else. The research is an attempt to shed light on Al-Ghitani’s method of employing the structure of reversal and switching, through analyzing samples from the texts of the novel. And the structure of (reverse and switching) emerged as a component of the method in building the miraculous world in (the manifestations), and extended to include the books of the novel, and manifested itself in: (Manifestations of travels, positions, positions, and conditions), and its effectiveness in producing meaning, casting the text, and weaving it This stylistic component contributes to the transition from sentence rhetoric to text eloquence.